Cladosiphon takenoensis sp. nov. (Ectocarpales s.l., Phaeophyceae) from Japan. Issue 4 (5th September 2016) - Kawai, Hiroshi; Hanyuda, Takeaki; Kim, Song‐Ho; Ichikawa, Yuki; Uwai, Shinya; Peters, Akira F.
SUMMARY: The new brown algal species Cladosiphon takenoensis H. Kawai (Chordariaceae, Ectocarpales s.l .) is described from Takeno, Hyogo, Japan based on morphology and DNA sequences. The species is a spring annual, growing on subtidal rocks at more or less exposed sites. It resembles C. umezakii in its gross morphology, and the two often grow together, but is distinguishable from C. umezakii in having a more hairy appearance. Cladosiphon takenoensis has a slimy, cylindrical, multiaxial and sympodial erect thallus, branching once to twice, and is provided with long assimilatory filaments (up to 1.8 mm long, composed of up to 100 cells). Unilocular zoidangia are formed on the basal part of assimilatory filaments. The species is genetically most related to C. umezakii and has the same basic thallus structures, but differs from C. umezakii and other Cladosiphon species in lacking phaeophycean hairs and plurilocular zoidangia of the assimilatory filaments. DNA sequences of the mitochondrial cox 1 and cox 3, chloroplast atp B, psa A, psb A and rbc L genes and the nuclear rDNA ITS2 region support the distinctness of the species. The genus Cladosiphon was paraphyletic in our analyses because the clades of C. okamuranus/C. zosterae and C. takenoensis/C. umezakii were split by Mesogloia vermiculata . However, since the genus‐level taxonomy of Chordariaceae needs considerable revision, we suspend the genus‐level taxonomy of the new species, and tentatively describe it as C. takenoensis .